PENYULUHAN PRAKTIK HIDUP BERSIH DAN SEHAT DI SEKOLAH SELAMA MASA PANDEMI COVID-19 - Ida Effendi (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
The prolonged state of the COVID-19 pandemic has a huge impact on all sectors, one of which is the education sector. Since pandemic stated, educational institutions have applied distance learning (PJJ) from pre-school to university level. In its implementation, PJJ is considered effective enough to be carried out in accordance with pandemic conditions. The negative impact of PPJ on student is difficulty in self development and hard to catch up so that limited face-to-face learning (PTM) begins. The purpose of community service activities (PkM) is to increase understanding and awareness of being obedient to health protocols during PTM consistently to prevent the transmission of COVID-19. The activity was given in the form of webinar counseling for students, parents and teachers of SMPIT Al Madinah, Bogor, West Java. Submission of material through presentations and interactively with questions and answers. The result of this PkM activity is an increase in knowledge and behavior in obeying health protocols during PTM. This service activity is needed and provides benefits to the community.